(untitled) (Revista Electrónica Calidad en la Educación Superior, 2016)
Every university which has interesting in create a new educational program, prior to the design of the curriculum or training proposal in this race, should undertake a study that will provide up to date and sufficient information on the educational, social and labor and institutional context of the race proposed by Ayala , Barrera, Bernal Diaz and Dominguez (2007). This article presents the required information in the analysis stage, prior to the design of the curriculum of a new career. For this purpose, carried out a description of the phases the first two phases of curriculum proposed by Diaz et al (2008) and the key inputs required for the preparation of studies of social relevance of new careers in some countries in the Latin American context. It is necessary to explain the contributions of information for the preparation of justification of the educational program in three dimensions: a) external dimension, b) internal dimension and c) administrative dimension. The target audience are those scholars who are interested in developing new offerings and, prior must assess the social relevance of them.